Novel treatments for compatibility of plant fiber and starch by forming new hydrogen bonds. (1st June 2018) - Zhang, Chuan-Wei; Li, Fang-Yi; Li, Jian-Feng; Li, Yan-Le; Xu, Jie; Xie, Qi; Chen, Shuai; Guo, An-Fu
Abstract: Cross-reaction of oxidization and plasticization was employed to prepare thermoplastic oxidized starch (TPOS). Oxidized ureal plant fiber (OUF) was prepared by soaking the plant fiber in H2 O2 and treating it with urea at low temperature (−15 °C). X-ray diffraction analysis showed that the crystallinity index of TPOS decreased from 19.95% to 0.89%. Amorphous starch more easily combined with the plant fiber. Moreover, infrared spectrum analysis indicated that the OH stretching vibration peak of the TPOS/OUF composite moved to 3375.4 cm −1 from 3414.0 cm −1, which revealed that new hydrogen bonds were formed in the TPOS/OUF composite. The H atoms of the OH groups in starch and plant fiber were oxidized to highly polar H + . The N atoms in urea and O atoms in glycerol got quite close to these highly polar H + groups and experienced an unusually strong field, which are known as hydrogen bonds. The newly formed hydrogen bonds made the plant fiber compatible with starch. Compatibility was experimentally validated by microscopic observation. For industrial application, new green composites and products were prepared using the TPOS/OUF composite slurry through a pollution-free process. Highlights: Green composites were prepared by pollution-free process using renewable materials. Thermoplastic oxidized starch (TPOS) was prepared by oxidization and plasticization. Oxidized ureal plant fiber (OUF) was prepared by H2 O2 soaking and urea treated. New hydrogen bonds were formed in the TPOS/OUF composite. The newly formed hydrogen bonds caused compatibility of plant fiber with starch.